Community training and participatory action-research: mixed methodology for the architectural project (2020)
The training of professionals involves an integrated mission for universities’ internal processes among teaching, research, and social responsibility. The article presents the results of the research project “Amanecerá y veremos” which inspired actual projects developed by the researcher in the city of Ibagué (Tolima, Colombia). Its importance lies in inter-institutional liaison and professional training based on Participatory Action-Research (PAR). Beginning with an infrastructure improvement of the University of Tolima campus with community participation, through two phases. In Phase One, “It will be dawn and we will see-2012”, twenty-eight brainstorming proposals for the improvement of Ducuara Park were developed. Later, in 2014, Phase two: “Bio-architecture and sustainability” were achieved by the design and construction of an information module in a vertical garden, made with sustainable materials. The methodology was based on participatory developments by the Colombian Organization of Students of Architecture (OCEA) and the Social Latin American Workshops by the Latin American Coordinator of Students of Architecture (CLEA). This linked management enabled an unprecedented project of almost three thousand participants. Recently this methodology is used as a basis for the author’s doctoral thesis focused on the city for Latin American children.